2019
DOI: 10.1519/jsc.0000000000001788
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Strength Adaptations and Hormonal Responses After Two Different Multiple-Set Protocols of Resistance Training in Postmenopausal Women

Abstract: We studied the effects of two different resistance training (RT) multiple-set protocols (three and six sets) on muscle strength and basal hormones concentrations in postmenopausal women (PW). Thirty-four PW were randomly allocated into three groups: control (CT, n=12), low RT volume (LV = three sets for each exercise, n=10) and high RT volume (HV = six sets for each exercise, n=12). The LV and HV groups performed eight exercises of a total body RT protocol three times a week, at 70 % of one repetition maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 45 publications
1
51
0
2
Order By: Relevance
“…Additionally, higher-volume RT (HV-RT), beyond that recommended by public guidelines for RT (i.e. 1-3 sets per exercise) (ACSM, 2009;Garber et al, 2011), has been shown to promote superior gains in muscle mass (Schoenfeld et al, 2019), but not muscle strength gains (Nunes et al, 2016;Nunes et al, 2019;Schoenfeld et al, 2019). Regarding this, it would seem reasonable to assume that if W ′ is influenced by muscle mass, additional muscle mass gain with a HV-RT leads to additional W ′ gains when compared to a lower-volume…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, higher-volume RT (HV-RT), beyond that recommended by public guidelines for RT (i.e. 1-3 sets per exercise) (ACSM, 2009;Garber et al, 2011), has been shown to promote superior gains in muscle mass (Schoenfeld et al, 2019), but not muscle strength gains (Nunes et al, 2016;Nunes et al, 2019;Schoenfeld et al, 2019). Regarding this, it would seem reasonable to assume that if W ′ is influenced by muscle mass, additional muscle mass gain with a HV-RT leads to additional W ′ gains when compared to a lower-volume…”
Section: Introductionmentioning
confidence: 99%
“…Esses resultados podem sugerir alteração do balanço energético e proteico muscular, com possível lipólise e síntese proteica. Nunes et al (2019), também observaram que 3 séries a 70% 1RM produz o mesmo aumento de força muscular que 6 séries, após 16 semanas de treinamento, mesmo na ausência do aumento de testosterona e cortisol. Assim, o aumento de força muscular pode ter ocorrido devido ao aumento do recrutamento das unidades motoras (HUGHES et al, 2017;SCHOENFELD et al, 2017).…”
Section: Resultsunclassified
“…Entretanto, mesmo na ausência desta adaptação, o treinamento de força induz ganho de força e hipertrofia muscular em mulheres (HAKKINEN et al, 2000;LINNAMO et al, 2005). Os homens possuem níveis séricos de testosterona superior ao das mulheres e o seu aumento com o exercício de força está bem documentado, mas em mulheres é inconsistente (KRAEMER;RATAMESS, 2005;LINNAMO et al, 2005;VINGREN et al, 2010) e a resposta hormonal aguda, ao exercício de força em mulheres, parece ser limitada (BENINI et al, 2015;BOSCO et al 2000;CONSITT et al, 2002;HAKKINEN et al, 2000;PAKARINEN, 1995;KRAEMER;RATAMESS, 2005;LINNAMO et al, 2005;LUK et al, 2019;NUNES et al, 2019;VINGREN et al, 2010). Poucos estudos demonstraram aumento de testosterona, em mulheres, após a realização do exercício de força (COPELAND et al, 2002;CUMMING et al, 1987;NINDL et al, 2001).…”
Section: Introductionunclassified
“…Although Gunay et al [43] specified that the insulin concentrations reduce in line with the secretion catecholamines during exercise, insulin levels were not affected by exercises after long-term aerobic and resistance training programs, by Gerosa-Neto et al [44] in the overweight/obese females and males, by Nunes et al [45] in menopausal females, by Timmons et al [37] in young nonathletes, and by Hecksteden et al [19] in healthy adult females and males. Similarly, in our study, no difference was found the insulin levels between the elite athletes and non-athletes in both male and female.…”
Section: Discussionmentioning
confidence: 99%